Knowledge management culture among the library staff of a private university/ Raja Abdullah Yaacob ... [et al.] - Yaacob, Raja Abdullah; Abidin, Anis Syazwani; Aminuddin, Nurfajariah; Iskandar, Raja Ahmad; Bunawan, AP Azli (Fakulti of Information Management, Universiti Teknologi MARA, 2015)
The emergence of knowledge management (KM) has led university libraries to realize the importance of its application for effectiveness and returns from its knowledge assets. Library as a treasure-house of human knowledge, participates in knowledge acquisition and organization, and becomes an important link in the knowledge innovation chain. However, changes towards KM require innovation in-knowledge culture among the staff because culture is a popular concept that explains the intangible and soft issues in organizations. The theory of organizational culture includes many aspects of culture, some of them invisible, like attitudes, beliefs, behavioral norms, basic assumptions and values, some of them visible, like systems and institutions, artifacts and products, rituals and behaviors. This paper reports the results of a case study of motivation and barriers to employees' participation in knowledge management culture and knowledge sharing at Limkokwing University of Technology and Creative Library. This study also investigates the staff awareness and their perceptions towards knowledge management culture. Apart from that, this paper attempts to look at the role of the staff in the development of knowledge culture within their departments and suggests a pragmatic approach to the implementation of knowledge management culture for academic libraries.